Antistatic agent
Patent Information
- Application Number
- JP2022067189
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-04-14
- Publication Date
- 2025-03-26
- Estimated Expiration
- 2042-04-14
AI Technical Summary
Conventional antistatic agents do not provide sufficient antistatic ability unless blended in large amounts, limiting their effectiveness in resin compositions.
A polycondensation product of an alcohol component containing aromatic or alicyclic diols and polyalkylene glycol with hydroxyl groups at both ends, and a carboxylic acid component, treated with a metal salt, is used to create a high molecular weight polyester resin with enhanced antistatic properties.
The antistatic agent exhibits low resistance and high antistatic ability, achieving effective charge dissipation with a smaller amount compared to conventional agents.
Smart Images

Figure 2023157340000001
Abstract
Description
Technical Field
[0001] The present invention relates to an antistatic agent to be incorporated into a resin composition used for resin molded products and the like in the field of the electronics industry and the like.
Background Art
[0002] In recent years, the development of the electronics industry has been remarkable, and the performance required for resin molded products used in this field has been increasing. Various resins are used for the exterior, housing, substrates, etc. of various electronic devices because of their excellent electrical insulation properties. However, due to their high insulation properties, there is a problem that they are easily charged by friction or the like. When the exterior or housing becomes charged, it becomes easy to attract dust and the like. Also, when an electronic substrate becomes charged, it causes malfunction of the device, etc., having many effects. Therefore, the resin used for electronic devices contains an antistatic agent and is designed to suppress charging.
[0003] Patent Document 1 discloses an invention relating to an antistatic resin composition obtained by mixing 1 to 30 parts by weight of a polyether ester obtained by condensing a poly(alkylene oxide) glycol having a number average molecular weight of 200 to 20,000, a glycol having 2 to 8 carbon atoms, and a polyvalent carboxylic acid and / or a polyvalent carboxylic acid ester having 4 to 20 carbon atoms with 99 to 70 parts by weight of an arbitrary thermoplastic resin.
[0004] Patent Document 2 discloses an invention relating to an antistatic agent which is a polyether ester (A) having an aromatic polyvalent carboxylic acid or its alkyl ester, a polyalkylene glycol, an alkylene diol, and a bifunctional phenol compound as essential raw material components, and the ratio of the number of alkylene groups derived from the alkylene diol in the polyether ester (A) to the number of aromatic nuclei derived from the bifunctional phenol compound is in the range of = 2 to 3,000.
[0005] Patent Document 3 discloses an invention relating to an antistatic agent characterized by comprising a polymer compound having a structure in which a diol, a dicarboxylic acid, a compound having an ethylene oxide chain with hydroxyl groups at both ends, and a polycarboxylic acid compound are linked via ester bonds. [Prior art documents] [Patent Documents]
[0006] [Patent Document 1] Japanese Patent Application Publication No. 6-57153 [Patent Document 2] Japanese Patent Publication No. 2000-192018 [Patent Document 3] Japanese Patent Publication No. 2016-44225 [Overview of the project] [Problems that the invention aims to solve]
[0007] However, conventional antistatic agents cannot sufficiently enhance the antistatic properties of a resin composition unless they are added in large quantities.
[0008] This invention relates to an antistatic agent with low resistance and high antistatic performance. [Means for solving the problem]
[0009] To solve the problems of the prior art described above, the inventors focused on high molecular weight compounds, i.e., resins, as antistatic agents, rather than low molecular weight compounds with antistatic properties such as surfactants. As a result, they found that using resins with a highly polar structure and further controlling the terminal structure of the polymer chains constituting the resin is effective in achieving an antistatic effect, and thus completed the present invention.
[0010] The present invention [1] An antistatic agent containing a polyester resin which is a polycondensate of an alcohol component containing an aromatic diol and / or alicyclic diol and a polyalkylene glycol having hydroxyl groups at both ends, and a carboxylic acid component, and in which the carboxyl groups are treated with metal chlorination, and [2] An antistatic agent containing a metal chloride polyester resin, which is a polycondensate of an alcohol component containing an aromatic diol and / or alicyclic diol and a polyalkylene glycol having hydroxyl groups at both ends, and a carboxylic acid component containing a metal salt of a carboxylic acid. Regarding. [Effects of the Invention]
[0011] The antistatic agent of the present invention exhibits the effects of low resistance and high antistatic performance. [Modes for carrying out the invention]
[0012] The antistatic agent of the present invention is a polycondensate obtained using a highly polar aromatic diol and / or alicyclic diol as the alcohol component and polyethylene glycol having hydroxyl groups at both ends, and is characterized by containing a polyester resin (polyester resin P) in which the carboxyl groups have been treated with metal chlorination.
[0013] The detailed reasons why the antistatic agent of the present invention exhibits excellent antistatic performance are not entirely clear, but they are thought to be as follows. Polyester resin is a polymer compound having numerous ester bonds in its main chain structure and is highly polar. Furthermore, the presence of carboxyl groups or hydroxyl groups at the ends of the polymer chain also contributes to its high polarity. For this reason, polyester resin has been conventionally used as an antistatic agent component in various resin molded products, focusing on this high polarity. It is known that using highly polar monomers as monomers constituting the polyester resin is effective in obtaining higher antistatic performance, but the inventors focused on the end groups of the polyester resin. This is because the end group portion has a higher degree of freedom compared to the central portion of the main chain, and is therefore thought to be able to act effectively on charge transfer. Therefore, by changing the carboxyl group among the end groups present in the polyester resin from the usual acidic type to a metal salt by introducing alkali metals, the end group portion, which has a high degree of freedom, can be made even more conductive, and it is presumed that this will result in a higher antistatic effect.
[0014] As described above, polyester resin P is a polycondensate of an alcohol component and a carboxylic acid component, and is a polyester resin in which the carboxyl groups in such polycondensate are treated with metal chlorination.
[0015] The alcohol component contains aromatic diols and / or alicyclic diols, from the viewpoint of maintaining the antistatic effect and the resin properties of the resin molded product containing the antistatic agent of the present invention.
[0016] As for aromatic diols, formula (I):
[0017] [ka]
[0018] (In the formula, OR and RO are oxyalkylene groups, R is an ethylene group and / or a propylene group, x and y represent the average number of moles of alkylene oxide added, and are positive numbers respectively. The value of the sum of x and y is 1 or more, preferably 1.5 or more, and 16 or less, preferably 8 or less, more preferably 6 or less, and even more preferably 4 or less.) The alkylene oxide adduct of bisphenol A represented by is preferred.
[0019] Examples of the alicyclic diol include hydrogenated bisphenol A, 1,4-cyclohexanedimethanol, 1,2-cyclohexanedimethanol, 1,4-cyclohexanediol, 1,2-cyclohexanediol, etc. Among these, hydrogenated bisphenol A or 1,4-cyclohexanedimethanol is preferred, and two or more kinds may be used in combination.
[0020] When the content of the aromatic diol or the alicyclic diol, or both are included, the total content of the aromatic diol and the alicyclic diol is preferably 50 mol% or more, more preferably 60 mol% or more, still more preferably 70 mol% or more in the alcohol component, and preferably 99 mol% or less, more preferably 98 mol% or less, still more preferably 97 mol% or less.
[0021] The alcohol component further contains a polyalkylene glycol having hydroxyl groups at both ends.
[0022] Examples of the polyalkylene glycol having hydroxyl groups at both ends include polyethylene glycol, polypropylene glycol, polytetramethylene glycol, etc. Among these, polyethylene glycol is preferred.
[0023] The number-average molecular weight of polyalkylene glycol having hydroxyl groups at both ends is preferably 100 or more, more preferably 500 or more, and even more preferably 800 or more, from the viewpoint of maintaining the antistatic effect and the resin properties of the resin molded product containing the antistatic agent of the present invention, and preferably 10,000 or less, more preferably 7,000 or less, and even more preferably 4,000 or less, from the viewpoint of the antistatic effect.
[0024] The content of polyalkylene glycol having hydroxyl groups at both ends is preferably 15% by mass or more, more preferably 25% by mass or more, even more preferably 35% by mass or more, and preferably 70% by mass or less, more preferably 60% by mass or less, and even more preferably 50% by mass or less, based on the total amount of alcohol and carboxylic acid components.
[0025] Alcohol components other than aromatic diols, alicyclic diols, and polyalkylene glycols include linear or branched aliphatic diols with 2 to 20 carbon atoms, and trivalent or higher alcohols.
[0026] Examples of carboxylic acid components include aromatic dicarboxylic acid compounds, linear or branched aliphatic dicarboxylic acid compounds, alicyclic dicarboxylic acid compounds, trivalent or higher aromatic carboxylic acid compounds, trivalent or higher aliphatic or alicyclic carboxylic acid compounds, etc. Carboxylic acid compounds include not only carboxylic acids but also anhydrides that decompose during the reaction to produce acids, and alkyl esters with 1 to 3 carbon atoms.
[0027] Examples of aromatic dicarboxylic acid compounds include phthalic acid, isophthalic acid, terephthalic acid, anhydrides of these acids, and alkyl esters of these acids with 1 to 3 carbon atoms.
[0028] Examples of aromatic carboxylic acid compounds with a valency of 3 or higher include trimellitic acid, 2,5,7-naphthalentricarboxylic acid, pyromellitic acid, anhydrides of these acids, and alkyl esters of these acids with 1 to 3 carbon atoms.
[0029] The content of aromatic carboxylic acid compounds, including aromatic dicarboxylic acid compounds and aromatic carboxylic acid compounds with a valency of 3 or higher, is preferably 70 mol% or more, more preferably 85 mol% or more, even more preferably 90 mol% or more, and even more preferably 95 mol% or more, and 100 mol% or less, in the carboxylic acid component.
[0030] The alcohol component may contain a monohydric alcohol, and the carboxylic acid component may contain a monohydric carboxylic acid compound, as appropriate.
[0031] The equivalent ratio (COOH group / OH group) of the carboxyl group of the carboxylic acid component to the hydroxyl group of the alcohol component is preferably 0.6 or higher, more preferably 0.7 or higher, even more preferably 0.75 or higher, and preferably 1.2 or lower, more preferably 1.15 or lower.
[0032] Polyester resins can be produced, for example, by polycondensing an alcohol component and a carboxylic acid component in an inert gas atmosphere, preferably in the presence of an esterification catalyst, and optionally in the presence of an esterification co-catalyst, polymerization inhibitor, etc., preferably at a temperature of 120°C to 250°C.
[0033] Examples of esterification catalysts include tin compounds such as dibutyltin oxide and tin(II) 2-ethylhexanoate, and titanium compounds such as titanium diisopropylate bistriethanolamine. The amount of esterification catalyst used is preferably 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, and preferably 1.5 parts by mass or less, and more preferably 1 part by mass or less, per 100 parts by mass of the total amount of alcohol and carboxylic acid components. Examples of esterification co-catalysts include gallic acid. The amount of esterification co-catalyst used is preferably 0.001 parts by mass or more, more preferably 0.01 parts by mass or more, and preferably 0.5 parts by mass or less, and more preferably 0.1 parts by mass or less, per 100 parts by mass of the total amount of alcohol and carboxylic acid components. Examples of polymerization inhibitors include 4-tert-butylcatechol. The amount of polymerization inhibitor used is preferably 0.001 parts by mass or more, more preferably 0.01 parts by mass or more, and preferably 0.5 parts by mass or less, and more preferably 0.1 parts by mass or less, based on 100 parts by mass of the total amount of alcohol and carboxylic acid components.
[0034] In this invention, the polyester resin may be a polyester resin that has been modified to such an extent that its properties are not substantially impaired. Examples of modified polyester resins include polyester resins that have been grafted or blocked with phenol, urethane, epoxy, etc., by methods described in Japanese Patent Publication No. 11-133668, Japanese Patent Publication No. 10-239903, Japanese Patent Publication No. 8-20636, etc.
[0035] The softening point of the polyester resin before the carboxyl groups are treated with metal chlorination is preferably 50°C or higher, more preferably 60°C or higher, even more preferably 90°C or higher, and preferably 200°C or lower, more preferably 185°C or lower, and even more preferably 170°C or lower.
[0036] The acid value of the polyester resin before the carboxyl groups are treated with metal chlorination is preferably 10 mg KOH / g or more, more preferably 15 mg KOH / g or more, even more preferably 20 mg KOH / g or more, and preferably 70 mg KOH / g or less, more preferably 50 mg KOH / g or less, even more preferably 40 mg KOH / g or less, and even more preferably 35 mg KOH / g or less.
[0037] The softening point and acid value of the polyester resin can be appropriately adjusted depending on the type and amount of raw material monomers used, as well as manufacturing conditions such as reaction temperature, reaction time, and cooling rate. One type of polyester resin may be used alone or two or more types may be used. When two or more types of polyester resins are used in combination, it is preferable that the physical properties of the mixture are within the aforementioned range.
[0038] From the viewpoint of antistatic effect, the polyester resin P is preferably an amorphous polyester resin. The crystallinity of a resin is expressed by a crystallinity index defined by the ratio of the softening point to the maximum endothermic peak temperature measured by a differential scanning calorimeter, i.e., the value of [softening point / maximum endothermic peak temperature]. A crystalline resin is a resin with a crystallinity index of 0.6 or higher, preferably 0.7 or higher, more preferably 0.9 or higher, and 1.4 or lower, preferably 1.2 or lower, more preferably 1.1 or lower. On the other hand, amorphous resins are those in which no endothermic peak is observed, or, if observed, those with a crystallinity index greater than 1.4, preferably greater than 1.5, more preferably 1.6 or higher, or less than 0.6, preferably 0.5 or lower. The crystallinity of the resin can be adjusted by the type and ratio of raw material monomers, as well as the manufacturing conditions (e.g., reaction temperature, reaction time, cooling rate). The maximum endothermic peak temperature refers to the temperature of the peak with the largest peak area among the observed endothermic peaks.
[0039] Carboxylate metal chlorination treatment refers to a treatment process in which the carboxyl groups in polyester resin P form metal salts.
[0040] Examples of metal salts formed by carboxyl groups in polyester resin P include alkali metal salts such as lithium, potassium, and sodium, and alkaline earth metal salts such as magnesium, calcium, and barium, with alkali metal salts being more preferred. Treatment may also be performed using two or more of these metal salts. Therefore, the metal chlorination treatment of carboxyl groups in polyester resin P is preferably performed with at least one alkali metal selected from the group consisting of lithium, potassium, and sodium.
[0041] Any known method may be used for the metal chlorination treatment of the carboxyl groups. For example, methods using metal hydroxides include adding a metal hydroxide to a molten polyester resin obtained by synthesis at a high temperature, and adding an aqueous solution of metal hydroxide to a polyester resin dissolved in an organic solvent. Of these, from the viewpoint of efficiently obtaining a polyester resin in which the terminal carboxyl groups are metal-chlorinated, the method of adding an aqueous solution of metal hydroxide to a polyester resin dissolved in an organic solvent is preferred. Examples of organic solvents used to dissolve the polyester resin include ketone solvents such as acetone and dialkylketones having an alkyl group with 1 to 3 carbon atoms, such as methyl ethyl ketone; ether solvents such as dibutyl ether and tetrahydrofuran; and ester solvents such as ethyl acetate and isopropyl acetate. Among these, dialkylketones having an alkyl group with 1 to 3 carbon atoms, such as acetone and methyl ethyl ketone, are preferred, and methyl ethyl ketone is more preferred.
[0042] The metal chlorination treatment is preferably carried out so that the metal chlorination degree of the carboxyl groups of the polyester resin P is 30 mol% or more and 100 mol% or less. From the viewpoint of antistatic performance, the metal chlorination degree is more preferably 50 mol% or more, even more preferably 70 mol% or more, and even more preferably 90 mol% or more. Here, the degree of metallic chloride is expressed as the proportion of carboxyl groups in the polyester resin P that have been treated with metal chloride. For example, when metal chloride treatment is performed using a metal hydroxide, the degree of metallic chloride is calculated using the following formula.
[0043]
number
[0044] In the present invention, the polyester resin P may be a metal chloride polyester resin obtained using a monomer in which the carboxylate group is a metal salt, such as sodium terephthalate, as the carboxylic acid component used in the synthesis of the polyester resin. That is, a metal chloride polyester resin which is a polycondensate of an alcohol component containing an aromatic diol and / or an alicyclic diol and a polyalkylene glycol having hydroxyl groups at both ends, and a carboxylic acid component containing a metal salt of a carboxylic acid.
[0045] The softening point of the polyester resin P is preferably 50°C or higher, more preferably 60°C or higher, even more preferably 65°C or higher, and preferably 200°C or lower, more preferably 160°C or lower, and even more preferably 125°C or lower.
[0046] The content of polyester resin P in the antistatic agent of the present invention is preferably 50% by mass or more, more preferably 70% by mass or more, even more preferably 90% by mass or more, and 100% by mass.
[0047] In addition to the polyester resin P, other additives may be incorporated into the antistatic agent of the present invention, provided they do not hinder the effects of the present invention. Specifically, these include various surfactants such as anionic, cationic, nonionic, and amphoteric surfactants; olefin rubbers such as ethylene propylene rubber; inorganic fillers and pigments such as talc; antioxidants; and antibacterial agents.
[0048] From the viewpoint of the material properties of the resin molded product, the resin composition containing the antistatic agent of the present invention is preferably one that includes a thermoplastic resin such as ABS resin (acrylonitrile-butadiene-styrene resin), polypropylene, polyethylene, polystyrene, polyethylene terephthalate, or polymethyl methacrylate.
[0049] There are no restrictions on the method of incorporating the antistatic agent of the present invention into a resin composition as an antistatic agent; known methods such as kneading and coating can be used. However, from the viewpoint of fully exhibiting the antistatic performance of the antistatic agent of the present invention, it is preferable to use kneading. For example, when kneading into a resin composition containing a thermoplastic resin, the antistatic agent of the present invention is added to the powdered resin composition, then mixed with a Henschel mixer or Nauter mixer, and if necessary, pelletized using a kneading extruder. The resulting mixture is then molded using an injection molding machine to obtain a resin composition in which the antistatic agent has been added by kneading.
[0050] The amount of the antistatic agent of the present invention is not particularly limited, but for example, it is preferably 1% by mass or more and 20% by mass or less in a resin composition containing a thermoplastic resin. Because the antistatic agent of the present invention has high antistatic ability, a high antistatic effect can be obtained even with a smaller amount compared to conventional antistatic agents. [Examples]
[0051] The present invention will be specifically described below with reference to examples, but the present invention is not limited in any way by these examples. The physical properties of resins, etc., can be measured by the following methods.
[0052] [Number average molecular weight of polyalkylene glycols] It is calculated from the hydroxyl value measured according to JIS K 1557.
[0053] [Softening point of resin] Using a flow tester "CFT-500EX" (manufactured by Shimadzu Corporation), 1 g of sample is heated at a heating rate of 6°C / min while a load of 1.96 MPa is applied by a plunger, and the sample is extruded from a nozzle with a diameter of 1 mm and a length of 1 mm. The amount of plunger descent of the flow tester is plotted against temperature, and the temperature at which half of the sample has flowed out is defined as the softening point.
[0054] [Maximum peak temperature of endothermic resin] Using a differential scanning calorimeter "Q-20" (manufactured by T.A. Instruments Japan Co., Ltd.), 0.01 to 0.02 g of the sample is weighed into an aluminum pan and cooled from room temperature (20°C) to 0°C at a rate of 10°C / min. The sample is then maintained at this temperature for 1 minute. Subsequently, the endothermic peaks are measured while the temperature is increased to 180°C at a rate of 10°C / min. Among the observed endothermic peaks, the temperature of the peak with the largest peak area is defined as the maximum endothermic peak temperature.
[0055] [Acid value of resins] The measurement will be performed according to the method of JIS K0070:1992. However, the measurement solvent will be changed from the mixed solvent of ethanol and ether specified in JIS K0070:1992 to tetrahydrofuran.
[0056] Polyester resin manufacturing example 1 A four-necked flask equipped with a nitrogen inlet tube, dehydration tube, stirrer, and thermocouple was purged with nitrogen. The alcohol components, carboxylic acid components other than trimellitic anhydride, esterification catalyst, and esterification co-catalyst shown in Table 1 were added. Under a nitrogen atmosphere, the mixture was heated to 235°C while stirring and held at 235°C for 3 hours. Then, the pressure inside the flask was further reduced and held at 8.3 kPa for 1 hour. After that, the mixture was returned to atmospheric pressure and cooled to 220°C. Trimellitic anhydride was added and held at 220°C for 1 hour. Next, the pressure inside the flask was reduced and the reaction was carried out at 8.3 kPa until the desired softening point was reached, yielding amorphous polyester resins (resins A1, A2, A4-A6). Resin A1 will be used as an antistatic agent in Comparative Example 2 in the test example described later.
[0057] Polyester resin manufacturing example 2 The inside of a four-necked flask equipped with a nitrogen inlet tube, dehydration tube, stirrer, and thermocouple was purged with nitrogen. The alcohol components, carboxylic acid components other than fumaric acid, esterification catalyst, and esterification co-catalyst shown in Table 1 were added. Under a nitrogen atmosphere, the mixture was heated to 235°C while stirring and held at 235°C for 3 hours. Then, the pressure inside the flask was further reduced and held at 8.3 kPa for 1 hour. After that, the mixture was returned to atmospheric pressure and cooled to 190°C. Fumaric acid and polymerization inhibitor were added, and the mixture was heated to 210°C over 2 hours. After being held at 210°C for 1 hour, the pressure inside the flask was further reduced and the reaction was carried out at 8.3 kPa until the desired softening point was reached, yielding amorphous polyester resin (resin A3).
[0058] Polyester Reservoir Manufacturing Example 3 A four-necked flask equipped with a nitrogen inlet tube, dehydration tube, stirrer, and thermocouple was purged with nitrogen. The alcohol components, carboxylic acid components other than trimellitic anhydride, esterification catalyst, and esterification co-catalyst shown in Table 1 were added. Under a nitrogen atmosphere, the mixture was heated to 235°C while stirring and held at 235°C for 3 hours. Then, the pressure inside the flask was further reduced and held at 8.3 kPa for 1 hour. After that, the mixture was returned to atmospheric pressure and cooled to 215°C. 184 g of trimellitic anhydride was added and held at 215°C for 1 hour. Next, the pressure inside the flask was reduced and the reaction was carried out at 8.3 kPa until the desired softening point was reached, yielding an amorphous polyester resin (resin A7).
[0059] The physical properties of the obtained resins are shown in Table 1. Attempts were also made to measure the maximum endothermic peak temperature, but no endothermic peaks were observed for any of the resins.
[0060] [Table 1]
[0061] Example 1 100g of resin A1 was placed in a four-necked flask equipped with a reflux condenser, a stirrer ("Three One Motor BL300" (manufactured by Shinto Kagaku Co., Ltd.)), and a thermocouple, and mixed with 100g of methyl ethyl ketone at 30°C to dissolve the resin. Next, 38.5g of 5% by mass sodium hydroxide aqueous solution was added, enough to metal-chloride all carboxyl groups of resin A1, and the mixture was stirred for 60 minutes. After that, the temperature was raised to 65°C, and the methyl ethyl ketone was removed by distillation while gradually reducing the pressure from 80kPa to 30kPa. When the amount of methyl ethyl ketone removed exceeded 50g, the temperature was further increased under reduced pressure, and finally the temperature was raised to 150°C, and the methyl ethyl ketone was removed by reducing the pressure while the resin composition remained molten. After cooling to room temperature, the mixture was vacuum-dried for a further 12 hours to obtain a metal-chlorinated polyester resin.
[0062] Examples 2-9 and Comparative Example 1 A metal chloride polyester resin was obtained in the same manner as in Example 1, except that the type of amorphous polyester resin and the type and amount of metal hydroxide aqueous solution used were changed as shown in Table 2.
[0063] Test example Using the metal chloride polyester resin obtained in the examples and comparative examples as an antistatic agent, 13 parts by mass of the antistatic agent and 87 parts by mass of ABS resin (Toyolac 100, manufactured by Toray Industries, Inc.) were mixed, and the mixture was injection molded using an injection molding machine (Japan Steel Works J-75E type) heated at 230°C to produce a 100 mm × 100 mm × 3 mm test piece made of a thermoplastic resin composition containing an antistatic agent.
[0064] Furthermore, as Comparative Example 2, test specimens were prepared in the same manner using resin A1 as an antistatic agent. Also, as Reference Example 1, a 100mm x 100mm x 3mm test specimen was prepared by injection molding ABS resin (Toyolac 100, manufactured by Toray Industries, Inc.) directly using an injection molding machine (Japan Steel Works J-75E model) heated to 230°C.
[0065] The prepared test specimens were surface-cleaned by immersion in deionized water. The surface resistivity of the specimens, after wiping off the moisture, was measured using the following method to evaluate the antistatic performance of the antistatic agent. The results are shown in Table 2. A lower surface resistivity indicates better antistatic performance.
[0066] [Measurement of surface resistivity] The test specimens were vacuum-dried at room temperature for 24 hours, and then left to stand in a constant temperature and humidity room at 23°C and 50% humidity for 24 hours to allow them to adjust to humidity levels. Next, the surface resistivity (Ω / □) of the test specimens was measured in the constant temperature and humidity room using a high-resistance meter 4329A (manufactured by Agilent Technologies) when 500V was applied.
[0067] [Table 2]
[0068] Based on the above results, it can be seen that, compared to Comparative Example 1, which contained a metal-chlorinated polyester resin without polyalkylene glycol, and Comparative Example 2, which contained an amorphous polyester resin in which the carboxyl groups were not metal-chlorinated, the resin compositions in Examples 1 to 9 that contained a metal-chlorinated polyester resin as an antistatic agent exhibited lower resistance and higher antistatic performance. [Industrial applicability]
[0069] The antistatic agent of the present invention is suitably used in resin compositions used in resin molded products and the like in the electronics industry and other fields.
Claims
1. An antistatic agent comprising a polyester resin which is a polycondensate of an alcohol component containing an aromatic diol and / or alicyclic diol and a polyalkylene glycol having hydroxyl groups at both ends, and a carboxylic acid component, the carboxyl groups of which are treated with a metal chloride.
2. 2. The antistatic agent according to claim 1, wherein the degree of metal salification of the carboxyl groups of the polyester resin is from 30 mol % to 100 mol %.
3. 2. The antistatic agent according to claim 1, wherein the acid value of the polyester resin before the carboxyl group is treated with a metal salt is from 15 mgKOH / g to 70 mgKOH / g.
4. An antistatic agent comprising a metal chloride polyester resin, which is a polycondensate of an alcohol component containing an aromatic diol and / or alicyclic diol and a polyalkylene glycol having hydroxyl groups at both ends, and a carboxylic acid component containing a metal salt of a carboxylic acid.
5. 5. The antistatic agent according to claim 1, wherein the carboxylic acid component contains from 70 mol % to 100 mol % of an aromatic carboxylic acid compound.
6. 5. The antistatic agent according to claim 1, wherein the polyalkylene glycol has a number average molecular weight of 100 or more and 10,000 or less.
7. 5. The antistatic agent according to claim 1, wherein the content of the polyalkylene glycol is from 15% by mass to 70% by mass in the total amount of the alcohol component and the carboxylic acid component.
8. 5. The antistatic agent according to claim 1, wherein the metal chloride is at least one alkali metal selected from the group consisting of lithium, potassium and sodium.
9. 5. The antistatic agent according to claim 1, wherein the content of the aromatic diol or the alicyclic diol, or the total content of the aromatic diol and the alicyclic diol when both are contained, is 50 mol % or more and 99 mol % or less in the alcohol component.
10. The aromatic diol has the formula (I): 【Chemistry 1】 (In the formula, OR and RO are oxyalkylene groups, R is an ethylene group and / or a propylene group, x and y are the average number of moles of alkylene oxide added, each of which is a positive number, and the sum of x and y is 1 or more and 16 or less.) 5. The antistatic agent according to claim 1, which is an alkylene oxide adduct of bisphenol A represented by the formula:
11. 5. The antistatic agent according to claim 1, wherein the alicyclic diol is hydrogenated bisphenol A and / or 1,4-cyclohexanedimethanol.